A imagem da mulher de meia-idade nos meios de comunicação social - Ferreira, Maria Francisca Theresa Pinto (1981)
The objective of this work was to study the degree of participation of the middle age woman in the media of social communication in Brazil. About 15 magazines, published by 'Bloch' and 'Abril Cultural', have been selected for ''this study. The readers basic characteristics and profiles have been obtained, from the publishers, for each one of the above mentioned magazines. The photographs and illustrations in the magazines were submitted to 'Content Analysis', being classified in three different groups - ' the young woman', 'the middle age woman', and 'the old woman' - by 14 randomly selected judges. After the classification the results were submitted to a logical and statistical analysis. It was also investigated the condition of the woman. considering the dimension of the biological, social and psychological level, and some aspects related to the mythicism of the feminine being. A short historical review about the woman situation in the social environment of Brazil is also presented, as some data about the Consumer's Psychology. From the gathered data it became clear that the incidence in the class 'middle age woman' is not significative, being almost all stimule in the class 'young woman', even in the media said to be directed to middle age women. The study shows that, independent of published matter and magazine, almost the totality of obtained stimuli is concentrated in the class 'The young woman'. 1- I t is presented, in the conclusion', that 'the middle age woman' does not exist as a form of social appeal, whit must contribute to maintain conflictive such a period as the climacteric.